On What Remains of a Life: Of Biography Writing and Its Significance - Klemczak, Stefan (B@belonline, 2022)
Biography writing seems a response to a central question of philosophical anthropology: What does a person do when they are unable to escape their finitude? They speak of their life or the life of others, trying to linger in human memory. Speaking of a life is joined to a question of identity and self-recognition. Biography writing covers a vast territory, stretching across literature, film, and scholarly studies, mainly historical and social. It has undergone historical shifts, gaining a new status in the modern world. These deliberations orbit around two questions: the ties between literature and biography writing and the history and ways of presenting a human life. A person, who will always be more what happens to them than what they do, remains a homo absconditus in biography writing. Yet tales of human fates allow us to better understand the human condition.